Is there a relationship between emotional Intelligence and students' mathematics learning outcomes? - Ramadhani, Diana Intan; Putranto, Sumbaji (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2022)
Students with good emotional Intelligence have adaptability and can develop social relationships with teachers and other students more easily. It is predicted to have an impact on student academic achievement. The study aims to determine whether there is a positive influence of emotional Intelligence on the mathematics learning outcomes of students at one of MAN in Yogyakarta on geometric lines and series. This study uses a quantitative approach to the type of correlational research. This research was conducted at one of MAN in Yogyakarta. The population in this study was class XI Agama 1 and XI Agama 2. The sampling technique used simple random sampling with a sample of 42 students. The instrument used in this study is a questionnaire of emotional Intelligence and a written test of learning outcomes, both of which had passed the content validity and reliability tests. The data analysis technique in this study uses simple regression analysis that has gone through classical assumption tests such as the normality test, heteroscedasticity test, and linearity test, followed by hypothesis testing such as t-test, coefficient of determination, and model interpretation. Data analysis was carried out with the help of the SPSS 25 software application. The results of this study indicate a positive influence of Emotional Intelligence on students' mathematics learning outcomes, with the magnitude of emotional Intelligence on learning outcomes of 12.8%, while other factors outside of this research influence the remaining 87.8%.